C77 EFFECT OF SACUBITRIL/VALSARTAN ON BOTH METABOLIC PARAMETER AND INSULIN RESISTANCE IN NON OBESE NON DIABETIC PATIENTS WITH HEART FAILURE. (18th May 2022) - Giofrè, F; Ventura, M; Sacchetta, L; Arturi, F; Clausi, C; Pelle, M; Zaffina, I; Lucà, S; Sciacqua, A; De Rosa, F; Cloro, C
Abstract: Background: Sacubitril/Valsartan has been shown to improve mortality and reduce hospitalizations in patients with heart failure with reduced ejection fraction (HFrEF). Moreover Sacubitril/Valsartan showed a significantly reduction in the HbA1c in diabetic patients. The effect of Sacubitril/Valsartan on metabolic parameter and insulin resistence in both, non obese and non diabetic patients, have not been previously described. Aim: We evaluated the effects of the Sacubitril/Valsartan on both glycaemic and metabolic parameter, on HOMA–IR and on echocardiographic parameters in patients with HFrEF. Methods: A total of 59 non obese and non diabetic patients with a diagnosis of HFrEF (EF < 35%) have been enrolled. All the patients underwent a complete anthropometrical evaluation, laboratory determinations (including fasting glucose, fasting insulin, HbA1c) and echocardiogram evaluation. Data analysis was made after 24 weeks of treatment. The insulin resistance has been assessed by HOMA–IR. Results: Data analysis demostrated a significant reduction in fasting plasma glucose (111.4 + 11.5 vs 106 + 10 mg/dl, P = 0.03), fasting plasma insulin (13.6 + 5.9 vs 10.5 + 4.4 µUI/ml), HbA1c value (6.14 + 0.5% vs 5.9 + 0.3%, P < 0.01) and insulin resistance (HOMA–IR, 3.74 + 2.2 vs 2.7 + 2.1, P = 0.03). The echocardiogram evaluation showed a significant reduction of the end–diastolic left ventricular volume (168 + 44 vs 150 + 38 ml, P < 0.05), a no significant reduction of the end–systolic left ventricular volume (98 + 26 vs 88 + 22 ml, P = 0.07), a significant reduction of E/e1 ratio and an average 7.8% increase in ejection fraction (EF), from a mean baseline of 32.3 + 2.4 to 40.1 + 3.8% (P < 0.0001). No differences in interventricular septal (IVS) thickness, posterior wall (PW) thickness, A–wave, E–wave and E/A ratio have been observed. No differences in anthropometrical parameters (weight, body mass index, waist circumference) and blood pressure were observed. Conclusions: Our data, even if preliminary, seem to indicate that sacubitril/valsartan might enhance glycaemic control and improve insulin resistance in non obese/non diabetic patients with HFrEF. Also, our data confirm that sacubitril/valsartan treatment is able to improve ejection fraction in HFrEF patients.